Utilizing virtual communities of practice in the national campaign of wheat in Egypt: action research - Mohamed Kassem; Laila Habaa; Fekry Aly; Rasha Shabana; Mohamed Farag; Naglaa Imaraa; Atwa Atwa (Discover Agriculture)
Abstract Background Virtual Community of Practices (VCoP) simply is a method to use social media in extension, yet its roots depend on a combination of four concepts: community of practice, social media, social learning theory, and pluralistic extension. The technical action research design was followed to put the VCoP into action and explore its profile. This study aimed to introduce a community of practice using social network applications to policy makers in the agricultural sector. Methodology Action research was conducted to validate the use of a VCoP in the National Campaign of Wheat in Egypt. A baseline survey, a content analysis of VCoP conversations, and an assessment study were used to collect the data. The frequency, range, percentage, mean, and average score were used for statistical analysis. Results The VCoP reached 22.22% and 10.40% of the wheat farmers in the two target villages, respectively. A high degree of knowledge exchange was detected among members, while messages crossed the VCoP borders as friends were invited to join the group. The VCoP helped its members establish new relationships with other stakeholders, and they expressed their need to expand membership to include other stakeholders. The media used in the VCoP was satisfactory; however, the need for more video messages and internet links was expressed. Extension agents believe that the VCoP complements other extension methods. Farmers see greater potential for cooperation than conflict, while bias is minimal among research, extension, traders, and company agents. Conclusions Farmers and other service providers in a village can be aggregated in a VCoP. This approach has proven to be valid as an extension community method for generating and sharing information with high “reach”. Coordination and training are essential for running and managing groups. Yearly programs, rather than seasonal programs, are more suitable for sustainability.